Exploring QSARs for inhibitory effect of a set of EGFR tyrosine kinase inhibitors by GA-MLR and molecular Docking simulations (British Journal of Multidisciplinary and Advanced Studies, 2024)
In this study, EGFR as a target for the anticancer activity of a series of 113 inhibitors were taken from the literature. Current work aims to derive statistically robust and appropriately validated multiple QSAR models using easily interpretable molecular descriptors and molecular docking analysis. It will be simpler to identify important structural trends and how they relate to anticancer activity as a result. The MLR model has been used to suggest some novel compounds with improved activity. It has been demonstrated how the predicted compounds interact with the enzyme using the docking study. All predicted compounds were discovered to have several hydrogen bonds with the receptor and involve their bulky groups in strong steric interactions with specific places of the enzyme. The proposed compounds exhibit good pharmacokinetic properties, according to the analysis of their pharmacokinetic profiles.